Kualitas Pelayanan di Kantor Desa Barangmamase Kecamatan Sajoanging Kabupaten Wajo - Lala Tasya Anjalika Syam; Burhanuddin Burhanuddin; Yuniarni Yuniarni; Darwis Darwis (Journal of Research and Development on Public Policy, 2026)
This research aims to describe the quality of service at the Barangmamase Village Office, Sajoanging District, Wajo Regency. The research uses a descriptive qualitative approach with five dimensions of SERVQUAL, namely tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (guarantee), and empathy (empathy). Data was obtained through interviews, observations, and documentation, with informants from village officials and the community. The results show that the dimensions of reliability and responsiveness obtained a good assessment, while the dimensions of empathy and assurance still need to be improved. The dimension of physical evidence shows that there are several deficiencies in the facilities available at the village office. Overall, the quality of service at the Barangmamase Village Office has shown quite good results, although it still needs to be improved in terms of assurance, empathy, and tangible to increase community satisfaction with public services. Based on the results of this study, it is suggested that the Barangmamase Village Office pay more attention to the aspects of empathy and assurance to increase community satisfaction.